Moderating effect of investor demand: privatized IPOs and flipping activity in the Pakistan IPO market. Issue 3 (15th June 2021) - Anwar, Ayesha; Mohd-Rashid, Rasidah
Abstract : Purpose: The purpose of this paper is to examine the impact of privatized initial public offerings (IPOs) on flipping activity in the Pakistan IPO market. Design/methodology/approach: This study sampled 95 IPOs listed on the Pakistan stock exchange over the period of 2000 to 2019. The ordinary least square technique and quantile regression were used to examine the impact of privatized IPO on flipping activity. Findings: The present study finds that privatization affects flipping activity and creates a quality signal in Pakistan's IPO market. The findings of this study also show that privatized IPOs were subjected to high levels of flipping activity compared to non-privatized IPOs. Additionally, investors' demand has been found to moderate the relationship between privatized IPOs and flipping activity in Pakistan's IPO market. Research limitations/implications: Based on the fact that the sample consists of a combination of privatized and non-privatized IPOs, the results provide valuable insight into factors that may lead to unusual trading behavior/flipping during the first day of listing. Originality/value: Despite several studies on events (e.g. short- and long-term price performance) around IPO, there is little evidence on how privatized IPOs affect flipping activity, which is a high volume of trading immediately after listing.